Complications of Acute Bacterial Rhinosinusitis in the Pediatric Population - Baumanis, Maraya M.; Honsinger, Kristen L.; Elmaraghy, Charles A.; Jatana, Kris R. (Journal of Pediatric Infectious Diseases, 2019)
Acute complicated sinusitis can occur in children and can lead to significant morbidity and mortality. While medical management is critical, it is important to provide multi-disciplinary care to involve surgical specialists. Since intracranial and extracranial complications can result from acute sinusitis, active communication among all these specialists is paramount to achieve the best patient outcomes. Children with these conditions are best managed at centers where appropriate pediatric medical and surgical subspecialty care is available.
Keywords: sinusitis; rhinosinusitis; acute complicated; intracranial; orbital; periorbital cellulitis; subdural empyema; epidural abscess; meningitis; cavernous sinus thrombosis